MILITARY-PATRIOTIC EDUCATION OF YOUNG PEOPLE IN CONDITIONS OF ACTIVE RECRUITING OF STUDENTS TO TERRORISTIC ORGANIZATIONS - Andrey P. Koshkin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article considers one of the most topical lines in military-patriotic education of young people which is characterized as work opposing students' recruiting to terroristic organizations. Special attention is paid to shaping a patriotic feeling as a basic unifying national idea, which counteracts students' recruiting to terrorists. The author shows the reasons for and conditions of possible successful enlisting of students to terroristic structures. He identifies the place and role of state and society, value and outlook standards and content of education programs, education and information technologies in confrontation with recruiting terrorists. Measures aimed at effective counteraction against recruiting campaign in students' masses were formulated.